2020
DOI: 10.7150/ijms.44285
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Promotes Stemness of Tumor Cells by Activating Smad/ID1 Signaling Pathway

Abstract: Background: IL-1β is reported to be involved in cancer development and distant metastasis. However, the underlying mechanism of IL-1β upon malignant behaviors remains largely unknown. In this study, we aimed to study whether IL-1β could enhance the stemness traits of tumor cells. Methods: The concentrations of serum IL-1β in head and neck squamous cell carcinoma (HNSCC) and melanoma patients were detected using ELISA assay. The effect and mechanisms of IL-1β on tumor cell growth, migration, invasion and stemne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Firstly, total RNA was extracted from tissue specimens and cell lines using TRIzol reagent as previously described 20 , 21 . Then complementary DNA was synthesized based on reverse transcription from total RNA using Takara cDNA Synthesis Kit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, total RNA was extracted from tissue specimens and cell lines using TRIzol reagent as previously described 20 , 21 . Then complementary DNA was synthesized based on reverse transcription from total RNA using Takara cDNA Synthesis Kit.…”
Section: Methodsmentioning
confidence: 99%
“…Total proteins from tissues specimens and cell lines were extracted using RIPA solution as previously described 20 , 21 . Briefly, total proteins were separated using SDS-PAGE and transferred to PVDF membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Investigations of salivary transcriptomic and proteomic biomarkers have shown that the concentration of IL-1β in combination with IL-8 was notably higher in OSCC patients compared to that in dysplasia patients [ 35 ]. As a result of its interaction with the activation of the Smad/ID1 signal pathway, IL-1β promotes the stemness, cancer development, and distant metastasis of HNSCCs [ 36 ]. IL-1β modulates Snail, which in turn causes the downregulation of E-cadherin and the upregulation of COX-2, resulting in the promotion of the EMT in HNSCCs under inflammatory conditions [ 37 ].…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…The ability of cancer cells to acquire a stem-like phenotype is a hallmark in tumors. Studies of molecular mechanisms have shown that IL-1β promotes the stemness of HNSCC and melanoma cells, through the activation of Smad/ID1 signalling pathways and the upregulation of stemness factor genes (Bmi1 and Nestin), thus increasing drug resistance [ 29 , 77 ]. This phenotype is critically associated with tumor progression and therapy failure.…”
Section: Il-1 and Resistance To Targeted Therapymentioning
confidence: 99%